PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA DOSEN DENGAN DIMEDIASI KOMITMEN ORGANISASI (Studi Kasus Pada Dosen Politeknik Ilmu Pelayaran Semarang) (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study was to examine the effect of motivation on the performance and competence of lecturers to be mediated by organizationalcommitmentin Marine Polytechnic state of Semarang. The population of this study is 98 lecturer of Marine Polytechnic State of Semarang. Analysis of the data was using double linear regression. Based on this study that themotivation positive and significant impact on organizational commitment, competence positive and significant effect on organizational commitment, motivation positive and significant effect on the performance of lecturers, competence positive and significant effect on the performance of lecturers.Organizational commitment positive and significant effect on the performance of lecturers. Organizational commitment did not mediate motivation on performance lecturer for the indirect effect is smaller than the direct effect, and organizational commitment did not mediate the competence of the lecturer's performance because the indirect effect is smaller than the direct effect. Key words: Organization commitment, motivation,competence, and lecturer performance